Modeling the relationship between the perceived negotiation styles and conflict management among physical education experts - Mojtaba Hasannejad; Ali Zareı; Farideh Ashrafganjoueı (Türk Spor ve Egzersiz Dergisi, 2017)
This study aims to modeling the relationship between the perception of negotiation and conflict management styles among physical education experts. The method of study is descriptive – correlation and it has conducted as a survey and a field study in terms of methodology. 217 out of 248 total number of distributed questionnaires were found suitable as the sample. Standard questionnaire of negotiation styles designed by Pierre was used as a measuring tool. Also, testing the conflict management strategies, standard questionnaire of Robbins was used. Using the factor analysis, the validity of the questionnaires was confirmed by a group of professors. And, reliability of the questionnaires was estimated with test-retest coefficient. The evaluations of the both negotiation styles and conflict management questionnaires are 0.78 and 0.73, respectively. Assessing the variables of the research, statistical tests such as Pearson correlation, regression and structural equation modeling were applied.  The results showed that there is a significant relationship between the styles of negotiation and conflict management. Also, the negotiation styles (analytical, normative and realistic) were able to account for variances related to conflict management. Furthermore, structural equation modeling confirmed the relationship between components of negotiation with conflict management. The findings of this research indicate that the conflicts within the organization will be properly managed, if the knowledge about negotiating skills and its styles increases. Proper communication through negotiations would result in reducing the destructive conflict in organizations.